Paeoniflorin Inhibits EMT and Angiogenesis in Human Glioblastoma via K63-Linked C-Met Polyubiquitination-Dependent Autophagic Degradation - Liu, Zhi; Wang, Zhaotao; Chen, Danmin; Liu, Xiaorui; Yu, Guoyong; Zhang, Yan; Chen, Chen; Xu, Ruxiang; Wang, Yezhong; Liu, Ru-en (Frontiers in Oncology, 2022)
Epithelial-to-mesenchymal transition (EMT) and angiogenesis have emerged as two pivotal events in cancer progression. Paeoniflorin has been widely studied in experimental models and clinical trials for cancer treatment because of its anti-cancer property. However, the underlying mechanisms of paeoniflorin in EMT and angiogenesis in glioblastoma was not fully elucidated. The present study aimed to investigate whether paeoniflorin inhibits EMT and angiogenesis, which involving c-Met suppression, while exploring the potential ways of c-Met degradation. In our study, we found that paeoniflorin inhibited EMT via downregulating c-Met signaling in glioblastoma cells. Furthermore, overexpressing c-Met in glioblastoma cells abolished the effects of paeoniflorin on EMT. Moreover, paeoniflorin showed anti-angiogenic effects by suppressing cell proliferation, migration, invasion and tube formation through downregulating c-Met in human umbilical vein endothelial cells (HUVECs). And c-Met overexpression in HUVECs offset the effects of paeoniflorin on angiogenesis. Additionally, paeoniflorin induced autophagy activation involving mTOR/P70S6K/S6 signaling and promoted c-Met autophagic degradation, a process dependent on K63-linked c-Met polyubiquitination. Finally, paeoniflorin suppressed mesenchymal makers (snail, vimentin, N-cadherin) and inhibited angiogenesis via the identical mechanism in an orthotopic xenograft mouse model. The in vitro and in vivo experiments showed that paeoniflorin treatment inhibited EMT, angiogenesis and activated autophagy. What’s more, for the first time, we identified c-Met may be a potential target of paeoniflorin and demonstrated paeoniflorin downregulated c-Met via K63-linked c-Met polyubiquitination-dependent autophagic degradation. Collectively, these findings indicated that paeoniflorin inhibits EMT and angiogenesis via K63-linked c-Met polyubiquitination-dependent autophagic degradation in human glioblastoma.